Analisis Yuridis Pembuatan Surat Kuasa Membebankan Hak Tanggungan (SKMHT) oleh Notaris - Hariyanto Hariyanto; Nurmala Saputri (Legalitas: Jurnal Hukum, 2022)
This study aims to analyze the position of the Power of Attorney to impose Mortgage (SKMHT) made by a Notary and to analyze the legal implications of the Power of Attorney to impose Mortgage (SKMHT) made by a Notary. The method in this study is a normative research method using a conceptual approach and legislation. The results of this study include: First: The position of the Power of Attorney for Imposing Mortgage (SKMHT) using a notarial deed made by a Notary has been relegated to an under-handed deed, because specifically the authority to make a Power of Attorney for Imposing Mortgage (SKMHT) has been delegated to the Land Deed Maker Official. (PPAT) as stated in PP 37 of 1998 concerning Regulation of Land Deed Maker Officials (PPAT). Second: The legal implications of making a Power of Attorney for Imposing Mortgage (SKMHT) made by a notary in the form of a notarial deed cannot be used as perfect evidence. The form of SKMHT is only determined based on PMNA/Perkaban Number 3 of 1997 as amended by Perkaban Number 8 of 1997. SKMHT made in the form of a Notary deed contains defects because it does not comply with the requirements of a Notary deed as stipulated in Article 38 of the Law on Notary Positions ( UUJN) The authority of a Notary is to make or create a deed, if a Notary makes a SKMHT by filling in the fields provided by the BPN, the SKMHT made by a Notary in this way does not have perfect evidentiary power.